Local economic impacts of national park visitors spending: The development process of an estimation method - Huhtala, Maija; Kajala, Liisa; Vatanen, Eero (Finnish Forest Research Institute, 2010)
The local economic impacts of national parks and other nature recreation areas have recently aroused a growing interest. Due to the lack of practical methods, however, the results from the few case studies that have been made have neither been comparable nor easy to achieve. Based on this background the Finnish Forest Research Institute and Metsähallitus have in co-operation built an application for estimating the local economic impacts of national parks and other nature recreation areas. The U.S. MGM2 model has served as an archetype for the Finnish application, which largely relies on Metsähallitus visitor monitoring system. The application produces comparable economic impact information across areas and over time. It also enables the annual follow-up of the impacts. This paper describes the development process including the problems faced on the way and the solutions found. It also shortly presents the method and the results. The first park-specific results show that the local income and employment effects vary a lot between the national parks. The next step will be to integrate the method to the Metsähallitus customer database.
Appendix 1 updated 8 April 2010.
Keywords: kansallispuisto; luonnon virkistyskäyttö; taloudelliset vaikutukset; tulovaikutukset; työllisyysvaikutukset; economic impact; employment effect; income effects; national parks; nature recreation